Réponses

2013-05-07T20:26:08+02:00

Pour les premier exercices tu les tape directement à la calculatrice et pour le 4 c'est comme celui-ci.

 

Ex 3:

 

A= 5(x-1)+3(x+1)

= 5x-5+3x+1

=8x-4

 

B= 2(x+8)-(x-6)

= 2x+16-x+6

= x+22

 

C= 7/3(x-3)-4/3(x-6)

= 7/3x-7-4/3x-8

= x-15

 

D= (x+5)(x+2)

= x²+2x+5x+10

= x²+7x+10

 

E= (5/3x+6/5)(5/6x+3)

= 25/18x²+5x+x+18/5

= 25/18x²+6x+18/5

 

F= (2x-4)(3x+5)-(4x-3)(7x+1)

= 6x² +10x-12x-20

= 6x²-2x-20

 

G= (t-4)(6t+7)-(2t-5)(3t+8)-5t²+5(t+4)

= 6t²-11t-28-6t²-t+40-5t²+5t+20

= -5t²-7t+32